The concept of God in preschool children: its relation with the children´s God concept that the catechist´s attributes them (Revista de Psicología, 2019)
Research was conducted on the correlation between the knowledge/awareness preschool teachers have about the background knowledge of their students regarding the concept of God, and what the student’s actually know about God.A descriptive methodology was used. A dialogue was established between the information gathered from two sources: the results obtained from a series of interviews with five-year-old children and the data resulting from a survey addressed to all preschool teacher-catechists who work in catholic schools which belong to the Archdiocese of Buenos Aires.The results have shown little correspondence between what the teacher believes the infantsknow and what they actually know or think. Therefore, we could claim that the knowledgethe teachers reveal and handle about the background knowledge that their students bringshould be reinforced.
Keywords: psychogenesis; concept of God; background knowledge; religious education